Shape the international discourse of Humanities Exchange in China's sports events within The Belt and Road Initiative - Jin Huang; Shaojie Wang; Bo Jiang (Quality in Sport)
This study takes the humanities exchange of sports events as the research object, uses the literature method, the historical method and the logical analysis method to deeply interpret the essence of the humanities exchange of sports events in China and the challenges of The Times. Through the "Belt and Road" platform, based on the current situation of cooperation and exchange of sports events in China, it strives to explore the new practice of humanities exchange of sports events with Chinese characteristics in the new era. It is concluded that the humanities exchange in Chinese sports events boosted by the "Belt and Road" will play a positive role in promoting China's international image, enhancing the international discourse power of sports, realizing the "people-to-people connection" with countries along the Belt and Road, and consolidating the soft power of Chinese sports culture. Therefore, the humanities exchanges of sports events in China should take the "Belt and Road" as the ideological guidance, carry out scientific and strategic layout of sports events in China and countries and regions along the routes, and strive to build brand sports events with Chinese characteristics in the new era. The purpose of this study is to promote the cooperation and development of sports diplomacy, enhance the discourse power of Chinese sports events in the international arena, and provide theoretical reference for promoting China's development to a sports power.